Dynamics of sugar beet root, crown and leaves mass with regard to plant densities and spring nitrogen fertilization - Varga, Ivana, agronomka (Array, 2020)
This study analyzes the dynamics of sugar beet root, crown, and leaves fresh and dry matter (FM and DM, respectively) accumulation per plant and their mass ratio at different plant densities and nitrogen fertilization. The biennial field trials were set as four different planting densities (60,000, 80,000, 100,000 and 140,000 plants ha-1) and three methods of nitrogen application in spring: control – without nitrogen fertilization (N0), presowing only (N1), and presowing with topdressing (N2). Close to the maturation, the mean DM of the whole root, crown, and leaves on September 20, 2014 amounted to 28.8, 7.3 and 4.0 t ha-1, respectively, whereas it amounted to 20.7, 4.1 and 2.3 t ha-1 in 2015, respectively. Moreover, with regard to the plant densities, the highest root DM was at 140,000 and 100,000 (31.6 t ha-1 in 2014 and 22.4 t ha-1 in 2015), compared to the wider plant densities of 80,000 and 60,000 plants ha-1 (22.4 t ha-1 in 2014 and 18.1 t ha-1 in 2015). Nitrogen fertilization positively influenced on dry matter accumulation, but it was different within the years. On September 20, 2014, a presowing fertilization (N1) increased the root DM by 17%, compared to the control, whereas in 2015 the presowing with topdressing (N2) increased the root DM by 30%. The root-to-leaves FM ratio amounted to 1:3.9 on May 30, 2014, whereas it amounted to 1:0.1 on September 20, 2014. The leaves FM was at its largest on June 20, 2015, when the root-to-leaves ratio amounted to 1:1.1, and gradually decreased to 1:0.1 on September 20, 2015.